Aplikasi Website Indeks Kepuasan Masyarakat (Studi Kasus: Kelurahan Panarung) - Priskila, Ressa; Sari, Nova Noor Kamala; Surana, Yogi Andy Pratama (Journal of Information Technology and Computer Science, 2022)
Service performance appraisal is now starting to become a benchmark for achieving quality service by evaluating every service and piece of information provided. The provision of questionnaire sheets is currently considered less effective in determining the satisfaction index of services due to storing data on questionnaire results and re-recording the results that have been filled in by the community. Therefore, this study aims to build a website to improve the work system with the aim of increasing the efficiency of the community satisfaction index. In designing the Community Satisfaction Index (IKM) Website, Panarung Village uses the waterfall method with stages: requirements definition, system and software design, implementation and unit testing, integration and system testing, operation and maintenance. This website has been tested with black box testing, and the results show that the features on the website can run well. The Panarung Village Community Satisfaction Index (IKM) website can be used as evaluation material for the performance of services in the Pahandut sub-district and also as a means of information such as news data, graphs, survey results, and criticism suggestions.